Using 21st century diagnostics to overcome barriers for lung function testing in primary care: it is time to consider oscillometry - Janwillem W. H. Kocks; Grietje H. Prins; Samuel Bardsley; Deesha Ghorpade; Sundeep Salvi (npj Primary Care Respiratory Medicine)
Obstructive airways diseases, including asthma and COPD as the most commonly encountered respiratory diseases in primary care, are both diagnosed by lung function testing using spirometry as the gold standard. However, this test is not always available in primary care practices and if it is, it is a difficult test to perform, requiring extensive operator training and patient co-operation with multiple forced manoeuvres. These barriers can lead to underdiagnosis and misdiagnosis, which further contributes to increased suffering and mortality associated with asthma and COPD. Oscillometry uses oscillating pressure waves to measure airflow obstruction and provides an alternative diagnostic test which is quicker and simpler than spirometry, requiring little training and no forced manoeuvres. Moreover, it provides additional aspects of lung function measurement which are not obtained by spirometry, making it a valuable option in primary care for diagnosing asthma and COPD.